PENGARUH LATIHAN SHADOW 8 TERHADAP AGILITY PADA PEMAIN BULUTANGKIS PB. MUSTIKA BANJARBARU USIA 12 – 15 TAHUN - Taufiq Rahman; Herita Warni (Multilateral : Jurnal Pendidikan Jasmani dan Olahraga, 2017)
This study aimed to determine the effects of exercise on agility in shadow 8 badminton players PB. Mustika Banjarbaru Age 12-15 Years. The method used is a method of pre-experiment design. The population in this study are all badminton player PB. Mustika Banjarbaru Age 12-15 Years of 10 people, while the sample in this study of 10 people with a sampling technique using total sampling.The results showed that the data pretest agility on a badminton player PB. Mustika Banjarbaru Age 12-15 Years gained an average = 7.1850 seconds with a standard deviation = 0.50423.  At posttest data is agility in badminton player PB. Mustika Banjarbaru Age 12-15 Years gained an average = 6.7500 seconds with a standard deviation = 0.44850. Results obtained by t test obtained t = 8.184> t table (9; 0.025) = 2.262, with Sig. (2-tailed) = 0,000; turns Sig. (2-tailed) <0.05  the t-count is significant. The conclusion that there was an effect on agility drills on shadow 8 badminton players PB. Mustika Banjarbaru Age 12-15 Years.Keywords: Effects, Exercise, Shadow 8, Agility and Badminton